Contrasting allocation patterns in wheat and weeds: allometric belowground and reproductive investment versus optimal partitioning adaptations - Xi, Jiazhen; Shi, Shengtao; Rong, Yizhong; Liu, Jie; Zhang, Li (Frontiers in Plant Science, 2025)
IntroductionModeling differences in biomass allocation between wheat and weeds—specifically to shoots (aboveground biomass), roots (belowground biomass), and seed mass (reproductive biomass)—enhances our understanding of sustainable weeds management. However, few studies have examined how fertilization and planting density influence biomass accumulation and allocation at both vegetative and reproductive stages within a wheat-weed community.MethodsTo address this gap, we conducted a greenhouse experiment growing wheat (Triticum aestivum L.), wild oats (Avena fatua L.), and barnyard grass (Echinochloa crusgalli (L.) P. Beauv.) under varying planting densities (4, 8, 12, and 16 individuals per pot) and fertilization treatments (1.018 g N per pot of urea). After six months of vegetative growth and one additional month at the reproductive stage, we measured aboveground and belowground biomass at both stages, and reproductive biomass during the reproductive stage.Results and DiscussionWe found that the biomass of wheat and weeds increased with fertilization but decreased with higher planting density, with no interactions between these factors. Wheat allocated more biomass to roots than shoots and more to reproductive than vegetative biomass, regardless of fertilization or planting density, following allometric allocation theory. In contrast, weeds distributed biomass similarly between shoots and roots at planting densities of 4 and 12 under fertilization or allocated more biomass to roots than to shoots at these densities. Additionally, some weeds achieved higher yields at both small and large sizes under planting densities of 12 and 16, respectively, suggesting greater phenotypic plasticity. This study provides a comprehensive analysis of biomass allocation differences between wheat and weeds throughout their life cycles, offering insights into plant adaptation strategies and practical applications for optimizing agricultural management.